2014
DOI: 10.1002/hbm.22595
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and brain gray matter volumes in a general population sample

Abstract: Alexithymia is perceived as a personality construct involving deficits in the cognitive processing of emotion. Brain areas that process emotions might be structurally altered in affected people. Subjects from the Study of Health in Pomerania who underwent whole body magnetic resonance imaging were investigated. After quality control procedures 2,589 subjects with Toronto Alexithymia Scale 20 (TAS-20) data and interview-based information on major depressive disorder (MDD) were available. After exclusion of stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 47 publications
3
42
0
7
Order By: Relevance
“…Similarly, previous studies reported either smaller [Borsci et al, ; Grabe et al, ; Ihme et al, ] or larger [Zhang et al, ] volumes of the insula, whereas others did not observe alexithymia‐related differences in this structure [Heinzel et al, ; Kubota et al, ; Sturm and Levenson, ]. Smaller amygdala volume was observed in two studies [Grabe et al, ; Ihme et al, ], while others failed to find differences in amygdala volume [Borsci et al, ; Heinzel et al, ; Kubota et al, ].…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Similarly, previous studies reported either smaller [Borsci et al, ; Grabe et al, ; Ihme et al, ] or larger [Zhang et al, ] volumes of the insula, whereas others did not observe alexithymia‐related differences in this structure [Heinzel et al, ; Kubota et al, ; Sturm and Levenson, ]. Smaller amygdala volume was observed in two studies [Grabe et al, ; Ihme et al, ], while others failed to find differences in amygdala volume [Borsci et al, ; Heinzel et al, ; Kubota et al, ].…”
Section: Introductionmentioning
confidence: 76%
“…Kugel et al reported a negative correlation between TAS‐20 (i.e., cognitive) alexithymia scores and amygdala reactivity to masked emotional faces [Kugel et al, ], a finding that was replicated by Reker et al, who used the same paradigm and additionally observed reduced automatic activation of the insula [Reker et al, ]. Although not identified in all studies [e.g., Heinzel et al, ; van der Velde et al, ], both the amygdalae and the insulae have indeed been found to differ in volume as a function of alexithymia by previous VBM studies employing the TAS‐20 scale (and thus assessing the cognitive alexithymia dimension): Ihme et al reported reduced left amygdala ROI volume in 17 high‐ compared to 17 low‐scorers on alexithymia [Ihme et al, ], a finding that was confirmed by a recently published large‐scale study, which reported reduced gray matter volumes in the right amygdala and the left insula in 844 male participants [Grabe et al, ]. Moreover, several studies reported differences in insula volume in relation to high levels of alexithymia [Borsci et al, ; Goerlich‐Dobre et al, ; Ihme et al, ; Zhang et al, ].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The template was then used to normalize the images into the standard Montreal Neurological Institute (MNI) space using the “DARTEL Normalize to MNI Space” program, utilizing the “preserve amount” option to retain the volumetric data of the original images. Finally, spatial smoothing was performed with an isotropic Gaussian kernel of 8mm full-width at half maximum [59,60]. …”
Section: Methodsmentioning
confidence: 99%